In vitro and in vivo resistance of Lactobacillus rhamnosus GG carried by a mixed pineapple (Ananas comosus L. Merril) and jussara (Euterpe edulis Martius) juice to the gastrointestinal tract. (February 2019) - de Almeida Bianchini Campos, Renata Cristina; Martins, Eliane Maurício Furtado; de Andrade Pires, Bruno; do Carmo Gouveia Peluzio, Maria; da Rocha Campos, André Narvaes; Ramos, Afonso Mota; de Castro Leite Júnior, Bruno Ricardo; de Oliveira Martins, Aurélia Dornelas; da Silva, Roselir Ribeiro; Martins, Maurilio Lopes
Abstract: This study evaluated the viability of Lactobacillus rhamnosus GG (LGG) and its in vitro and in vivo resistance to the gastrointestinal tract (GIT) when carried by a mixed fermented pineapple and jussara juice. The effects of product ingestion on the biochemical characteristics of the blood and on the development of aberrant crypt foci (ACF) in Wistar rats were also determined. The LGG viability in probiotic juice was higher than 7.2 log CFU/mL throughout 28 days at 8 °C. The mean count of the probiotic microorganism in the fecal samples of the rats was 5.6 log CFU/g, identical to the count at the end of the in vitro trial (enteric phase II), indicating that the mixed pineapple and jussara juice was an excellent vehicle for LGG. No difference ( p  > .05) was verified to ACF among the groups. However, the results for the probiotic culture viability and its in vitro and in vivo resistance to the gastrointestinal tract suggest that this juice is an excellent carrier matrix for LGG and contributed to a reduction in the levels of the LDL (low density lipoprotein) fraction of the blood cholesterol, thus being an aid in the control of coronary diseases. Graphical abstract: Unlabelled Image Highlights: The product elaborated contained an elevated antioxidant potential. The levels of Lactobacillus rhamnosus GG remained above 10 7  CFU/mL during 28 days at 8 °C; Mixed juice of pineapple and jussara was an optimum vehicle for Lactobacillus rhamnosus GG. Viability and resistance to the GIT both in vitro and in vivo were accessed; The juice conformed to the FAO survival requirements for a probiotic.